Blast Exposure, White Matter Integrity, and Cognitive Function in Iraq and Afghanistan Combat Veterans - Ivanov, Iliyan; Fernandez, Corey; Mitsis, Effie M.; Dickstein, Dara L.; Wong, Edmund; Tang, Cheuk Y.; Simantov, Jessie; Bang, Charlene; Moshier, Erin; Sano, Mary; Elder, Gregory A.; Hazlett, Erin A. (Frontiers in Neurology, 2017)
The long-term effects of blast exposure are a major health concern for combat veterans returning from the recent conflicts in Iraq and Afghanistan. We used optimized diffusion tensor imaging (DTI) tractography algorithm to assess white matter (WM) fractional anisotropy (FA) in blast-exposed Iraq and Afghanistan veterans (n=40) scanned on average 3.7 years after deployment/trauma exposure. Veterans diagnosed with a blast-related mild traumatic brain injury (mTBI) were compared to combat veterans with blast exposure but no TBI diagnosis. Blast exposure was associated with decreased FA in several WM tracts. However, total blast exposure did not correlate well with neuropsychological testing performance and there were no differences in FA based on mTBI diagnosis. Yet, veterans with mTBI performed worse on every neurocognitive test administered. Multiple-linear regression across all blast-exposed veterans using a six-factor prediction model indicated that the amount of blast exposure explained 11-15% of the variability in composite FA scores such that as blast exposure increased, FA decreased. Education explained 10% of the variability in composite FA scores and 25-32% of FA variability in the right cingulum, such that as level of education increased, FA increased. Total blast exposure, age, and education were significant predictors of FA in the left cingulum. We did not find any effect of PTSD on cognition or composite FA. In summary, our findings suggest that greater total blast exposure is associated with poorer WM integrity. While FA was not associated with neurocognitive performance, we hypothesize that FA changes in the cingulum in veterans with multiple combat exposures and no head trauma prior to deployment may represent a marker of vulnerability for future deficits. This, however, needs to be examined longitudinally.